1972
DOI: 10.1128/iai.5.5.637-644.1972
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility of Male and Female Mice to Encephalomyocarditis Virus: Effects of Castration, Adrenalectomy, and the Administration of Sex Hormones

Abstract: Male mice have been noted to be more susceptible to encephalomyocarditis (EMC) virus than female animals. Castration of male mice abolished this difference and resulted in enhanced resistance similar to that of female mice. This increase in resistance in castrated males could be eliminated by adrenalectomy. Adrenalectomy alone increased susceptibility in male mice but not in female mice. The administration of a long-acting preparation of testosterone markedly increased susceptibility both in castrated male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

1973
1973
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 27 publications
(27 reference statements)
1
17
1
Order By: Relevance
“…Estrone stimulates the replication of both viruses and appears to make previously resistant tissues susceptible to MM virus. DISCUSSION Previous studies indicate that certain steroids enhance experimental viral infections, whereas others have little or no effect (1,2,4,8,10,11). The present study, however, has shown that the VIE activity of a hormone may be dependent on the viral agent used for challenge.…”
Section: Resultscontrasting
confidence: 62%
“…Estrone stimulates the replication of both viruses and appears to make previously resistant tissues susceptible to MM virus. DISCUSSION Previous studies indicate that certain steroids enhance experimental viral infections, whereas others have little or no effect (1,2,4,8,10,11). The present study, however, has shown that the VIE activity of a hormone may be dependent on the viral agent used for challenge.…”
Section: Resultscontrasting
confidence: 62%
“…Also, female backcross progeny consistently were more resistant than their male counterparts. Enhanced resistance to various viral and bacterial pathogens of female as compared with male mice has been well documented (17)(18)(19)(20)(21)(22). It also has been shown in immunized outbred Swiss mice challenged i.c.…”
Section: Discussionmentioning
confidence: 95%
“…Alternately, hormonal differences may make the pancreas in the male more susceptible to virus-induced injury. In this connection, it is known that EMC virus produces more severe disease and higher mortality in males than females (16). The observation that hyperglycemia persists in the males for many months after infectious virus can be recovered from the pancreas suggests that the infection produces acute beta cell damage that in some cases results in permanent impairment of function.…”
Section: Discussionmentioning
confidence: 99%